Kualitas dan Potensi Dadih Sebagai Tambahan Pendapatan Peternak Kerbau di Kabupaten Kerinci - Afriani, Afriani (Fakultas Peternakan Universitas Jambi, 2008)
An experiment was conducted to know process of production, quality and potency of curd (dadih) as source additional income of buffalo farmer in Kabupaten Kerinci. The survey was done in three district (kecamatan) at Kabupaten Kerinci, kecamatan Air Hangat, Gunung Kerinci, and Kayu Aro. There were 28 farmer’s buffalo from 3 district that made curd. Evaluation of dadih quality was done after 3 days fermentation, include moisture content, acidity, protein, fat, and total plate count bacteria of dadih. The results showed that the farmer’s additional income was about Rp 1,787.639,97 per lactation period or total curd production was about 52.21 kg per lactation. The Curd that made from farmer’s in three districts Kabupaten Kerinci has same quality.